Does vocational training help young people find a (good) job? - Werner Eichhorst (IZA World of Labor, 2014)
Youth unemployment has increased in many industrialized countries following the recent global recession. However, this reflects not only the cyclical shock, but also the crucial role of institutions in structuring the transition from school to work. Vocational training, in particular in a dual form combining vocational schooling and structured learning on-the-job, is often considered to be one of the most important policy solutions in combating youth unemployment. The evidence available supports this perception, but the institutional requirements of a successful training system also have to be taken into account from a policy perspective.
Keywords: M53; J13; 330; youth unemployment; vocational education and training; dual vocational training; apprenticeships